Estilos de crianza y la expresión oral de los niños de 3 años de la I.E 1564 “Radiantes Capullitos”- 2017 - De La Cruz Rodríguez, Juanita Lorena (2018)
The purpose of this research was to present the relationship of parenting styles in the development of the oral expression of children of 3 years of the initial level._x000D_ For the elaboration of the investigation, by means of the technique of the observation, the deficit in the development of the expression of the children of 3 years of the I.E. 1564 "Radiantes Capullitos". In this case, the design used for the investigation was of a correlational descriptive type._x000D_ During the research carried out, two instruments were applied to determine the level of development of oral expression in 3-year-old children and the type of parenting predominant in the parents._x000D_ It had a total population of 391 children, carried out with a sample of 130 children at the age of 3 years of the classrooms: roses, tulips, orchids, alelí and violets. Also worked with the amount of 130 parents for the application of the same._x000D_ The results obtained after the present investigation with a margin of error of 0.05% was that the null hypothesis was accepted, concluding that there is a negative relationship of parenting styles of the parents in the oral expression developed in the boys and girls of 3 years of EI 1564 "Radiantes Capullitos”.